Engineering properties of diphenyl - Anderson, Kermit.; U.S. Atomic Energy Commission.; Argonne National Laboratory. (Argonne National Laboratory, Reactor Engineering Division, 1953)
Data on the melting points of several binary systems containing diphenyl and for complex mixtures of diphenyl and its pyrolysis products are presented graphically. Graphs of viscosity versus composition at 130 degrees C for the systems are also presented.
At head of title: Argonne National Laboratory.
"August 11, 1953."
Includes bibliographical references.
Data on the melting points of several binary systems containing diphenyl and for complex mixtures of diphenyl and its pyrolysis products are presented graphically. Graphs of viscosity versus composition at 130 degrees C for the systems are also presented.
Data collected from the literature on the vapor pressure, enthalpy, liquid density, and vapor density of pure diphenyl are presented. A Mollier diagram, a temperature entropy diagram, and data on viscosity of diphenyl as a function of temperature are also presented.
Keywords: Vapor pressure.; Biphenyl / Thermal properties.; Viscosity.; Solubility.; Enthalpy.; Biphenyl.